Water conservation system practices at building in Klang valley / Nurul Huda Abd. Kadir - Abd. Kadir, Nurul Huda (Faculty of Architecture, Planning and Surveying, 2009)
This chapter discussed regarding problem arising on water conservation system practice in Klang Valley, the significance of study, research question was developed in this chapter, objectives of this study also clearly mentioned, the scope and limitation and thesis overview also revealed in this chapter.